Pregnancy following Unilateral Immediate Breast Reconstruction with Titanized Polypropylene Mesh (TiLOOP(R) Bra) without Compromising the Result. Issue 9 (September 2018) - Nolte, Elke; Klein, Evelyn; Paepke, Stefan
Abstract : Summary: Immediate breast reconstruction after mastectomy due to cancer or as a prophylactic treatment is widely preferred to avoid psychosocial distress, poor body image, and diminished sexual well-being. An increasing number of women undergoing breast reconstruction are in childbearing age; however, only limited data are available on the cosmetic outcome of patients undergoing implant-based breast reconstruction with a surgical mesh and subsequent pregnancy. This is a case report of a female patient who underwent unilateral implant-based breast reconstruction with a titanized surgical mesh implant (TiLOOP Bra). Twenty-two months after reconstruction, the woman delivered a healthy child. No adverse events occurred. The patient breastfed with the contralateral breast. The cosmetic result and patient-reported outcome was excellent. Pregnancy after breast reconstruction with a synthetic surgical mesh is not contradictory to an excellent cosmetic outcome.